Exchange of the Coronavirus Replicase Polyprotein Cleavage Sites Alters Protease Specificity and Processing - Gadlage, Mark J. (American Society for Microbiology (ASM), 2010)
Coronavirus nonstructural proteins 1 to 3 are processed by one or two papain-like proteases (PLP1 and PLP2) at specific cleavage sites (CS1 to -3). Murine hepatitis virus (MHV) PLP2 and orthologs recognize and cleave at a position following a p4-Leu-X-Gly-Gly-p1 tetrapeptide, but it is unknown whether these residues are sufficient to result in processing by PLP2 at sites normally cleaved by PLP1. We demonstrate that exchange of CS1 and/or CS2 with the CS3 p4-p1 amino acids in engineered MHV mutants switches specificity from PLP1 to PLP2 at CS2, but not at CS1, and results in altered protein processing and virus replication. Thus, the p4-p1 residues are necessary for PLP2 processing but require a specific protein or cleavage site context for optimal PLP recognition and cleavage.